Індивідуально-авторські засоби вербалізації категорії інтимізації в поетичному дискурсі Василя Симоненка - Космеда, Тетяна; Kosmeda, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
В. Симоненко належить до поетів української лінгвокультури, який майстерно вербалізував категорію інтимізації, використовуючи традиційні (звертання, займенникові форми, фольклорі конструкції) й індивідуально-авторські мовні засоби, серед яких оксюморон, виражений системою моделей, а також прийом скупчення однотипних граматичних форм (насамперед компаративних конструкцій) у межах одного контексту. Ці форми вносять у поетичний текст систему прагматичних смислів, моделюють прагматичні ефекти. The article sheds light on the problem of writers’ idio-style which is considered to be a hotly debated issue in modern Ukrainian linguistics. V. Symonenko, as a poet of the Ukrainian linguistic culture, has been recognized by many literary critics as «an intimate poet». The study argues that the poet is an unsurpassed master of using stylistic devices aimed at verbalization of the intimization concept – he combines both traditional (addresses, the pronoun forms, the folklore constructions) and his individual language means when creating his poetic images. Oxymoron, expressed by a system of models, is the most frequently used stylistic device. The use of one-type grammatical forms in one and the same context (mostly comparative constructions) is also considered to be one of such language expressive means. These language devices enrich a poetic text with the system of pragmatic meanings and model the pragmatic effects. The play on words, masterfully used by the poet, reflects his peculiar, unique individual perception of the world. In the article intimization is interpreted as a pragmatic category and is defined as a code of an individual manner of the writer, a stylistic device by means of which the author conveys the esthetics of the emotionally colored intellectual communication with a reader.
Individual Author’s Means of Intimization Concept Verbalization in V. Symonenko’s Poetic Discourse.
Keywords: лінгвокультура; категорія інтимізації; традиційні й індивідуально-авторські засоби; linguistic culture; intimization category; traditional and individual author’s means